The Psychonauts’ World of Cognitive Enhancers - Napoletano, Flavia; Schifano, Fabrizio; Corkery, John Martin; Guirguis, Amira; Arillotta, Davide; Zangani, Caroline; Vento, Alessandro (Frontiers in Psychiatry, 2020)
Background: There is growing availability of novel psychoactive substances (NPS), including cognitive enhancers (CEs) which can be used in the treatment of certain mental health disorders. Whilst treating cognitive deficit symptoms in neuropsychiatric or neurodegenerative disorders using CEs might have significant benefits for patients, the increasing recreational use of these substances by healthy individuals raises many clinical, medico-legal and ethical issues. Moreover, it has become very chal-lenging for clinicians to keep up-to-date with CEs currently available as comprehen-sive official lists do not exist. Methods: Using a web crawler (NPSfinder®), the present study aimed at assessing psychonaut fora/ platforms to better understand the online situation regarding CEs. We compared NPSfinder® entries with those from the European Monitoring Centre for Drugs and Drug Addiction (EMCDDA), and from the United Nations Office on Drugs and Crime (UNODC) NPS databases, up to spring 2019. Any substance that was iden-tified by NPSfinder® was considered a CE if it was either described as having nootropic abilities by psychonauts or if it was listed among the known CEs by Froestl and colleagues. Results: A total of 142 unique CEs were identified by NPSfinder®. They were divided into 10 categories, including plants/ herbs/ products (29%), prescribed drugs (17%), image and performance enhancing drugs (IPEDs) (15%), psychostimulants (15%), miscellaneous (8%), Phenethylamines (6%), GABAergic drugs (5%), cannabimimetic (4%), tryptamines derivatives (0.5%) and piperazine derivatives (0.5%). A total of 105 chemically different substances were uniquely identified by NPSfinder®. Only one CE was uniquely identified by the EMCDDA; no CEs was uniquely identified by the UNODC. Conclusions: These results show that NPSfinder® is helpful as part of an Early Warn-ing System, which could update clinicians with the growing numbers and types of nootropics in the increasingly difficult-to-follow internet world. Improving clinicians’ knowledge of NPS could promote more effective prevention and harm reduction measures in clinical settings.